Profile of Color Vision Defects in a Tertiary Care Hospital in Western Nepal - Godar, ST; Kaini, KR; Khattri, JB (Nepal Journal of Medical Sciences, 2014)
Background: Significant numbers of people suffer from color vision defect but most of the time remains an unnoticed problem. The present work was undertaken to study the profile of color vision defects in Western region of Nepal. Methods: This is a cross-sectional, hospital based study conducted in a tertiary care hospital of Western Nepal from January 2012 to December2012. Total of 971 patients were selected by simple random method. In each patient assessment of visual acuity and the examination of anterior segment and posterior segment was done. Color vision was tested by Ishihara Pseudo isochromatic chart. Results: Out of total 971 patients, 501 were males (51.59%) and 470were females (48.40%). Out of this total, 91 (9.37%) had color vision defects. Among the color vision defects patients,68were males (74.72%)and 23 were females (25.27%). Congenital color vision defect was seen in 10.97% of males and 2.97% of females whereas acquired color vision defect was observed in 2.57% of males and 1.91% of females respectively. Color vision defects were observed more in Chhetri (14.38%), followed by Brahmin (10.16%) and Magar caste (9.89%). Conclusion: The prevalence of color vision defect in Nepal is significant. All people should be screened for color vision defect and advised about it so that they can take special care in daily practice as well as in future life Nepal Journal of Medical Sciences | Volume 03 | Number 01 | January-June 2014 | Page 1-4 DOI: http://dx.doi.org/10.3126/njms.v3i1.10340